Pemodelan basis data untuk laporan penjualan wholesale kendaraan mobil. - Aam Shodiqul Munir; Rifqi Anugrah; Nurul Ilma Hasana Kunio; Elisabeth Christina Sari; Rizal Sapta Dwi Harjo (Lentera Dua Indonesia, 2021)
GAIKINDO or the Association of Indonesian Automotive Industries is a non-profit company or organization engaged in the automotive industry. A company can be said to be successful or not, it can be seen from one point of view, namely sales to the company. Sales is one of the important things for the company because it can support the company's growth. Due to the development of the times, the competition between companies is getting tougher, companies are required to be more creative in marketing their products, one way is to carry out a promotional activity to the public to convey the existence of products in the market. Every product that is sold must have product characteristics so that it can attract the attention of buyers. This study aims to analyze sales data at the GAIKINDO company to find out which of the categories, brands, specifications and others are the reasons for buyers to buy a car during the pandemic in January to December 2020. In addition, this study also aims to perform data modeling using car sales wholesale data obtained from GAIKINDO in January 2020 to December 2020. And to facilitate the search for car sales information based on specifications, brands and other categories. In data analysis using several data modeling techniques, namely sitemap and data flow diagram modeling to design the flow of the data to be modeled.